Analisis Peranan Sektor Pertanian, Kehutanan, Dan Perikanan Terhadap Pembangunan Kabupaten Lampung Tengah - Latif Alghifari, Abdul; Darsono, Darsono; Khairiyah, Refa'ul (JALOW | Journal of Agribusiness and Local Wisdom, 2022)
Regional economic development can not be separated from the contribution of the sector that forms GRDP. The agriculture, forestry, and fishery sector is the primary sector that made the highest contribution to the GRDP of Central Lampung Regency for the 2011-2020 period with an average was morethan 35%. The purposes of this research are to analyze the trend of contribution, basis or non basis, changing roles, and factors that cause role changes in the role of the agricultural sector. Forestry and fisheries in Central Lampung Regency in 2011-2020. The basic method of this research is descriptive analysis. The data used is secondary data. The data analysis used is (1) Contribution Trend through Simple Linear Regression, (2) Location Quotient (LQ), (3) Delta Location Quotient (âˆ†LQ), (4) Shift Share (SS). The results of this study indicate that the trend of the contribution of the agriculture, forestry, and fishery sector tends to decrease, but that result mean a good condition of economic development where the share of a good impact because the share of the secondary and tertiary sectors is increasing. The agriculture, forestry, and fishery sector is the basic sector because the LQ value > 1 and is included in the star category with the percentage of âˆ†LQ being positive and LQ > 1, so it is predicted that there will be no change in role and will remain the basic sector now and in the future. The result of shift share analysis shows that the LSS value > LSS, so that the role of the agriculture, forestry, and fishery sector is more influenced by location faktors than struktural faktors.